Idārat Jūdat al-Ishrāf al-Lughawiy fi Tarqiyat Ta'līm al-Lughah al-‘Arabiyah bi Ma'had Jāmi‘ah Maulāna Mālik Ibrāhīm al-Islāmiyyah al-Ḥukūmiyyah Malang - Bahroin Budiyah (Alsina : Journal of Arabic Studies, 2019)
There is quality management with education subject who teach and guide college students in Arabic learning. Mushrifs is the santri’s companion in the first and second semester in Mahad Al-Jami’ah. In particular program, they teach Arabic in Mahad and conduct Arabic learning. The quality of Mushrifs of Language in improving Arabic learning is one of the objectives in order to generate good and success mushrifs in Mahad Al-Jami’ah.        The research problems were: 1) How is the planning quality of language guidance in improving Arabic learning in mahad al-jami’ah, 2) how is the organization quality of language guidance in improving Arabic learning in mahad al-jami’ah, 3) how is the implementation of quality Supervision of language in improving the Arabic learning in mahad al-jami’ah, 4) how is the supervision quality of language guidance in improving Arabic learning in mahad al-jami’ah. This study aimed to describe the planning, organization, implementation, and supervision of quality management of mushrifs in improving the Arabic learning in Mahad Al-jam’ah. This study used descriptive analysis design, and the data collections were through observation, interview and documentation, and through all those things to research in data’s about the quality management of language guidance. The results of quality management of language guidance study in improving the Arabic learning were: 1) in the planning stage, the first process was opening the registration for mushrifs’ candidates with a very strict selection, 2) in the organization aspect was the cooperation relationship between the mahad director, murabbi, and mushrifs of language with their tasks, 3) in the implementation aspect was through PSDM, language enrichmen, shabah al-lugah, gebyar bahasa competition and bilingual seminar; 4)  and in the supervision aspect was the supervision was conducted once in two weeks by murabbi of language.